2008
DOI: 10.1002/hep.22565
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and tensin homolog (PTEN) regulates hepatic lipogenesis, microsomal triglyceride transfer protein, and the secretion of apolipoprotein B-containing lipoproteins

Abstract: HepaticapolipoproteinB(apoB)lipoproteinproductionismetabolicallyregulatedviathephosphoinositide 3-kinase cascade; however, the role of the key negative regulator of this pathway, the tumor suppressor phosphatase with tensin homology (PTEN), is unknown. Here, we demonstrate that hepatic protein levels of apoB100 and microsomal triglyceride transfer protein (MTP) are significantly down-regulated (73% and 36%, respectively) in the liver of PTEN liver-specific knockout (KO) mice, and this is accompanied by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 27 publications
(47 reference statements)
5
35
2
Order By: Relevance
“…Based on our results, steatosis development arises not only from an increased de novo lipogenesis and decreased VLDL export as shown by Qiu et al [26], but also from an increased FA uptake, as suggested by the significant upregulation of several FA transporters. This is linked with substantial changes in hepatic glucose metabolism, including enhanced glycolysis (whose products are essentially used for de novo lipogenesis), as well as decreased gluconeogenesis.…”
Section: Discussionsupporting
confidence: 84%
“…Based on our results, steatosis development arises not only from an increased de novo lipogenesis and decreased VLDL export as shown by Qiu et al [26], but also from an increased FA uptake, as suggested by the significant upregulation of several FA transporters. This is linked with substantial changes in hepatic glucose metabolism, including enhanced glycolysis (whose products are essentially used for de novo lipogenesis), as well as decreased gluconeogenesis.…”
Section: Discussionsupporting
confidence: 84%
“…Liver-specific deletion of PTP-1B improves hepatic insulin signaling, enhances insulin suppression of hepatic gluconeogenesis, and lowers circulating levels of TG and cholesterol. 58 Evidence that generation of PIP3 is necessary for insulinmediated suppression of VLDL is provided by recent studies of phosphatase and tensin homolog PTEN, 59 a lipid phosphatase that catalyzes removal of the 3′ phosphate of phosphoinositides. Data suggest that loss of PTEN and associated increases in cellular PIP3 result in suppressed VLDL secretion.…”
Section: Insulin Regulation Via Pip3 Signaling and Modulation By Membmentioning
confidence: 99%
“…Data suggest that loss of PTEN and associated increases in cellular PIP3 result in suppressed VLDL secretion. 59 In HepG2 cells expressing dominant negative PTEN, there is a 50% lowering of cellular and secreted B100. 59 Overexpression of PTEN renders cells unresponsive to insulin suggesting that rapid elimination of PIP3 by PTEN negates suppression.…”
Section: Insulin Regulation Via Pip3 Signaling and Modulation By Membmentioning
confidence: 99%
See 2 more Smart Citations